2003
DOI: 10.1046/j.1523-1755.2003.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Grade of chronic renal failure, and acute and long-term outcome after percutaneous coronary interventions

Abstract: In this retrospective cross-sectional study, even patients with slightly elevated serum creatinine levels of 1.3 to 1.4 mg/dL had a significantly reduced long-term outcome after PCI. Thus, even mild chronic renal failure appears to be associated with markedly increased risk after a PCI, with implications to the high number of patients concerned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 19 publications
5
52
0
Order By: Relevance
“…Reinecke et al 19 indicated that long-term mortality increased with higher creatinine levels, with a significant difference starting at a level of 1.3 mg/dl and higher. They claimed that the decrease in renal function might represent a sensitive indicator of general microangiopathy induced by the presence of cardiovascular risk factors, particularly hypertension and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Reinecke et al 19 indicated that long-term mortality increased with higher creatinine levels, with a significant difference starting at a level of 1.3 mg/dl and higher. They claimed that the decrease in renal function might represent a sensitive indicator of general microangiopathy induced by the presence of cardiovascular risk factors, particularly hypertension and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that patients with CKD are at increased risk of adverse cardiac events after stent implantation, 28,29 and the incidence of stent thrombosis was also reported to be associated with CKD after DES implantation. 30 However, there has been no study showing the association between NA and CKD.…”
Section: Ckd and Namentioning
confidence: 98%
“…† Furthermore, it appears that this increase in risk is present with even mild reduction in kidney function. 174,177,178 In high-risk populations, most but not all studies have suggested that decreased GFR is an independent risk factor for outcomes. This is true in the elderly, in whom even mild reductions of kidney function are associated with worse outcomes, 137 in studies of subjects with hypertension, 4 in studies of populations with a higher than normal prevalence of diabetes, 165 and among older patients undergoing general surgery.…”
Section: Reduced Gfrmentioning
confidence: 99%